Pengaruh Kinerja Keuangan, Kepemilikan Institusional dan Struktur Modal Terhadap Nilai Perusahaan Makanan Minuman di Bei - Vania Estherina; Diyan Lestari (UNIVERSITAS KALBIS, 2022)
The study aims to analyze the effect of financial performance, institutional ownership and capital structure on firm value. This study uses food and beverage sector companies listed on the Indonesia Stock Exchange in the period 2014-2018 as a sample, with total 10 companies that meet the criteria. The most appropriate model is common effect. Based on the hypothesis testing (t test), show that the variable of financial performance doesn’t effect the firm value, with a t-test value of 1.176337 which was smaller than the t-table of 2.01290 and probability of 0.2455. Institutional ownership does not influence the value of the company with t value of 1.038469 smaller than t table 2.01290 and probability 0.3045. Capital structure variables does not affect the value of the company with t value of -0.507314 which is smaller than the value of t table that is 2.01290 and the probability of 0.6144.